'Becoming Mozambicanised': Nostalgic amnesia among Zimbabweans adapting to 'disorder' in Mozambique. Issue 2 (3rd April 2017) - Hammar, Amanda
ABSTRACT: This article explores the ways in which displaced Zimbabweans who migrated to Mozambique's Manica Province in the 2000s in the wake of political and economic crisis, constructed a largely unreflective discursive dichotomy between remembered 'order' in Zimbabwe and perceived 'disorder' in Mozambique. It does so through the lens of two empirical domains of practice: that of public policy, and that of production and enterprise. Unpacking the complexities of these domains, and juxtaposing them in relation to a more realistic version of Zimbabwe, exposes the Zimbabweans' discursive over-simplifications and stereotypes. It suggests that rememberings and representations of an 'ordered' past in Zimbabwe set in contrast to a 'disordered' Mozambique, are part of a nostalgic amnesia that assists these ambivalent migrants to deal with (or deny) their displacement and losses, and helps them adapt to the new and strange 'disordered' present and to do the work of 'becoming Mozambicanised'.